2014
DOI: 10.1542/peds.2013-3698
|View full text |Cite
|
Sign up to set email alerts
|

Unconditional Regard Buffers Children’s Negative Self-Feelings

Abstract: BACKGROUND: Unconditional regard refers to the feeling that one is accepted and valued by others without conditions. Psychological theory suggests that experiences of unconditional regard lead children to feel that they are valuable despite setbacks. We hypothesized that reflecting on experiences of unconditional regard would buffer children’s negative self-feelings (eg, shame, insecurity, powerlessness) in the face of setbacks. To test this hypothesis, we randomized children to reflect on ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Also, failing students were less eager to learn than successful students. More importantly and in line with our hypotheses based on indirect evidence from previous research (e.g., Baldwin & Sinclair, 1996; Brummelman et al, 2014), we found that conditional regard magnifies success- and failure-induced changes in positive affect. When the regard of the experimenter was conditional, students who experienced success showed an increase in positive affect, whereas no significant change occurred when regard was not related to performance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, failing students were less eager to learn than successful students. More importantly and in line with our hypotheses based on indirect evidence from previous research (e.g., Baldwin & Sinclair, 1996; Brummelman et al, 2014), we found that conditional regard magnifies success- and failure-induced changes in positive affect. When the regard of the experimenter was conditional, students who experienced success showed an increase in positive affect, whereas no significant change occurred when regard was not related to performance.…”
Section: Discussionsupporting
confidence: 91%
“…One other field experimental study asked secondary school students to imagine a situation in which they experienced unconditional regard (i.e., regard provided regardless of students’ behavior or performance), conditional regard, or another social event. This study found that lower grades (received three weeks after the manipulation) only resulted in more negative feelings for students who had not imagined unconditional regard (Brummelman et al, 2014). …”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Such negative self-feelings, in turn, increase students' risk for later depression and anxiety (Sowislo & Orth 2013). Brummelman et al (2014a) designed a 15minute intervention to prevent secondary-school students from seeing failure as a threat to their self-worth. Students reflected on times when they were accepted and valued by others unconditionally.…”
Section: Kate Mary Bennett a And Gillian Windle B Amentioning
confidence: 99%
“…So, we want to empower young people, and we believe that once we give them reliable information and provide them room to discuss these issues, they can make their own choices. These approaches have been found effective in buffering the at-risk youth's negative self-image, cultivating a trusting relationship between the practitioner and the youth, and engaging the youth in healthy activities (Brummelman et al, 2014;Lee, 2013;Shea, & Jackson, 2015).…”
Section: Harm-reduction Approachmentioning
confidence: 99%